2011
DOI: 10.1111/j.1365-2559.2011.03808.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and pathological features of metastases of primary cutaneous desmoplastic melanoma

Abstract: The cellular composition of primary DM correlates with that of metastatic DM and with outcome. It is important to consider the possibility of primary or metastatic DM when examining tumours composed of spindle cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 22 publications
0
11
1
Order By: Relevance
“…10,13 However, histologic subtype was not evaluated in these two studies. 10 Murali et al 15,30 showed that SLN metastases occurred more often in mixed (8.5 %) versus pure (4.9 %) DM, although this was not a significant difference ( p = .25), and in a second study they found no significant predictors of SLN disease. Mohebati et al 16 reported on head and neck DM and found no SLN metastases in 15 and 8 patients with pure and mixed DM, respectively.…”
Section: Discussionmentioning
confidence: 96%
“…10,13 However, histologic subtype was not evaluated in these two studies. 10 Murali et al 15,30 showed that SLN metastases occurred more often in mixed (8.5 %) versus pure (4.9 %) DM, although this was not a significant difference ( p = .25), and in a second study they found no significant predictors of SLN disease. Mohebati et al 16 reported on head and neck DM and found no SLN metastases in 15 and 8 patients with pure and mixed DM, respectively.…”
Section: Discussionmentioning
confidence: 96%
“…22 In yet another series of patients with metastatic desmoplastic melanoma, the mixed subtype (hazard ratio 6.17; CI 1.61-23.81; P ¼ 0.019) was an independent predictor of poorer overall survival in a multivariate analysis. 28 Thus, the higher mortality of the mixed subtype appears to be well established. However, immunohistochemical and genetic differences between these groups have not been previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…DM patients represent an older population, and in our study, a considerable proportion of deaths with known causes were not due to melanoma, so it is not surprising that older age would be correlated with worse OS. Murali et al also reported that gender significantly predicted OS, [ 24 ] and two studies have correlated MR with survival [ 5 , 16 ]. In contrast to prior studies that have reported a significant association between histologic subtype and RFS or MSS, [ 2 , 3 , 8 ] our study did not find histologic subtype to be a significant predictor of RFS, MSS or OS on multivariable analysis.…”
Section: Discussionmentioning
confidence: 99%